Contributions of bile acids to gastrointestinal physiology as receptor agonists and modifiers of ion channels - Keely, Stephen J.; Urso, Andreacarola; Ilyaskin, Alexandr V.; Korbmacher, Christoph; Bunnett, Nigel W.; Poole, Daniel P.; Carbone, Simona E. (American journal of physiology: Gastrointestinal and liver physiology, 2022)
Bile acids (BAs) are known to be important regulators of intestinal motility and epithelial fluid and electrolyte transport. Over the past two decades, significant advances in identifying and characterizing the receptors, transporters, and ion channels targeted by BAs have led to exciting new insights into the molecular mechanisms involved in these processes. Our appreciation of BAs, their receptors, and BA-modulated ion channels as potential targets for the development of new approaches to treat intestinal motility and transport disorders is increasing. In the current review, we aim to summarize recent advances in our knowledge of the different BA receptors and BA-modulated ion channels present in the gastrointestinal system. We discuss how they regulate motility and epithelial transport, their roles in pathogenesis, and their therapeutic potential in a range of gastrointestinal diseases.